2015
DOI: 10.1002/adhm.201500606
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genomic Impact of Large and Small Lateral Dimension Graphene Oxide Sheets on Human Immune Cells from Healthy Donors

Abstract: Graphene oxide (GO) is attracting great interest in biomedical sciences. The impact of GO on immune cells is one fundamental area of study that is often overlooked, but critical in terms of clinical translation. This work investigates the effects of two types of thoroughly characterized GO sheets, different in their lateral dimension, on human peripheral immune cells provided from healthy donors using a wide range of assays. After evaluation of cell viability, the gene expression was analyzed, following GO exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 62 publications
2
96
0
Order By: Relevance
“…The authors also found that large GO promoted a pro-inflammatory polarization of macrophages both in vitro and in vivo . In contrast, other investigators have reported that small GO sheets elicited more profound effects on human immune cells (monocytes) when compared to large GO (58). Li et al (59) suggested, on the basis of experimental and theoretical studies, that micron-sized graphene sheets entered cells through membrane piercing or slicing (“edge-first” uptake).…”
Section: Effects On Macrophages: Breaking and Enteringmentioning
confidence: 66%
“…The authors also found that large GO promoted a pro-inflammatory polarization of macrophages both in vitro and in vivo . In contrast, other investigators have reported that small GO sheets elicited more profound effects on human immune cells (monocytes) when compared to large GO (58). Li et al (59) suggested, on the basis of experimental and theoretical studies, that micron-sized graphene sheets entered cells through membrane piercing or slicing (“edge-first” uptake).…”
Section: Effects On Macrophages: Breaking and Enteringmentioning
confidence: 66%
“…1 Carbon nanomaterials, such as carbon nanotubes (CNTs), graphene and carbon nanohorns (CNHs), have been studied for biomedical applications because of their unique characteristics. [2][3][4][5][6][7][8][9][10][11] Carbon nanomaterials are promising candidates for bone tissue engineering applications due to their superior cytocompatible, mechanical and electrical properties. [12][13][14][15][16][17][18] Some years ago, we initiated to explore study the applications of carbon nanomaterials for bone tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cationic lipid (R)-DOTAP is an immunologically active enantiomer of the DOTAP racemic mixture, and could initiate a strong immune response in an exogenous antigen model [70, 71]. Specific functionalization and different lateral side dimensions of graphene and carbon-based nanomaterials showed distinct impacts on immune cells, which would induce a specific activation of dendritic cells and monocytes and serve as a nanoadjuvant for the development of an effective antitumor immune response [7275]. In a recent study, Luo et al performed an in vitro screening of a series of ultra-pH sensitive copolymers containing tertiary amines with linear or cyclic side chains for their ability in generating CTL responses.…”
Section: Application Of Nanomaterials For Cancer Vaccine Designmentioning
confidence: 99%